Functionalized nanofiber hemodialysis membrane and preparation method, application and supporting equipment

Functional nanofiber hemodialysis membrane was prepared through electrospinning technology, combining metal-organic frame materials and active molecules, and solving the problems of low efficiency and insufficient function of the existing hemodialysis membrane, achieving efficient and multifunctional uremia toxin removal and Improved safety.

CN118558156BActive Publication Date: 2024-12-27JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410758734.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2024-12-27
Estimated Expiration
2044-06-13

AI Technical Summary

Technical Problem

The existing hemodialysis membranes are inefficient in removing uremia toxins and lack multiple functions, making it difficult to achieve antioxidant, anti-inflammatory, anticoagulant and antibacterial effects at the same time.

Method used

Functional nanofiber hemodialysis membranes were prepared by electrospinning technology, and metal-organic frame materials (MOFs, COFs, HOFs) were grown in situ on the surface of the nanofiber membrane, and antioxidant, anti-inflammatory and antibacterial activities were grafted on its surface. Molecules form multiple functional membranes.

Benefits of technology

It significantly improves the removal ability and removal rate of uremia toxins, enhances the antioxidant, anti-inflammatory, anticoagulant and antibacterial properties of the membrane, and reduces the occurrence of complications in patients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118558156B_ABST
    Figure CN118558156B_ABST
Patent Text Reader

Abstract

The present invention discloses a functionalized nanofiber hemodialysis membrane and a preparation method, application and supporting equipment. The preparation method comprises: S1: preparation of a nanofiber hemodialysis membrane precursor; S2: preparation of a nanofiber membrane loaded with crystals; S3: preparation of a high-efficiency functionalized nanofiber hemodialysis membrane; in addition, the present invention also provides the application of the nanofiber hemodialysis membrane in a hemodialyzer and a hemodialysis machine. The high-efficiency functionalized nanofiber membrane prepared by the present invention has multiple functions such as adsorption, anti-oxidation, anti-inflammatory, anti-coagulation and antibacterial, effectively improves the ability to remove uremic toxins, can quickly remove uremic toxins in the patient's body while reducing the patient's complications. This functionalized nanofiber membrane is simple to prepare, and the raw materials are easily available, and has broad prospects in the field of hemodialysis materials. In addition, the designed nanofiber hemodialyzer and portable hemodialysis machine are simple to operate and lightweight, which is convenient for patients to carry and operate independently.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nano new functional materials, and in particular to a method for preparing a highly efficient functionalized nano fiber hemodialysis membrane and its application in blood purification. Background Art

[0002] Hemodialysis is the most widely used treatment for patients with end-stage renal disease. Although a period of hemodialysis treatment can remove most toxins from the patient's body, dialysis cannot completely replace the function of normal glomeruli in the human body, which requires the improvement of existing hemodialyzers. Compared with traditional dialysis membranes or ultrafiltration membranes, ultrafiltration membranes made by electrospinning technology have a through-hole structure and a larger porosity. Under the same operating pressure conditions, the electrospun nanofiber ultrafiltration membrane has a larger flux and higher filtration efficiency. It can also be used as a nanoparticle carrier or functional modification platform to control its properties. It can quickly and effectively remove uremic toxins and achieve multiple physiological functions such as anti-oxidation, anti-inflammatory, anti-coagulation, and antibacterial. It has broad application prospects in the field of blood purification. Summary of the invention

[0003] The purpose of the present invention is to solve the technical problems existing in the prior art by providing a high-efficiency functionalized nanofiber membrane having multiple functions such as adsorption, anti-oxidation, anti-inflammation, anti-coagulation and antibacterial, and which can effectively improve the removal ability and removal rate of uremic toxins, as well as a hemodialyzer and hemodialysis machine used in conjunction with the membrane.

[0004] To achieve the above object, firstly, the present invention provides a method for preparing a functionalized nanofiber hemodialysis membrane, the method comprising the following steps:

[0005] S1: Preparation of nanofiber hemodialysis membrane precursor

[0006] The polymer and the solvent are mixed to obtain a polymer solution, wherein the mass fraction of the polymer is 8-20wt%; the organic ligand and the active molecule are respectively added to the above solution, heated and stirred until uniform to obtain an electrospinning solution, wherein the organic ligand is 8-20wt% of the mass fraction of the polymer, and the active molecule is 10-15wt% of the mass fraction of the polymer; the obtained spinning solution is injected into a spinning tube for electrospinning to obtain a nanofiber membrane;

[0007] S2: Preparation of crystal-loaded nanofiber membranes

[0008] S2.1: When the organic ligand in S1 is trimesic acid, terephthalic acid, 2-aminoterephthalic acid, pyromellitic acid or fumaric acid, the preparation method is as follows:

[0009] The zirconium metal salt and the organic ligand are added to the solvent respectively, and ultrasonic treatment is performed to obtain a uniform mixed solution; the nanofiber membrane obtained in S1 is immersed in the mixed solution for 10-30 minutes, and then a hydrothermal / solvothermal reaction is performed, and finally Zr-based MOFs are in situ grown on the surface of the nanofiber membrane to obtain a nanofiber hemodialysis membrane A, wherein the zirconium metal salt is zirconium oxychloride or zirconium chloride, and the concentration is 0.5-3M; the organic ligand concentration is 0.1-3.5M;

[0010] S2.2: When the organic ligand in S1 is trimesic acid or terephthalic acid, the preparation method is as follows:

[0011] The iron metal salt and the organic ligand are added to the solvent respectively, and after ultrasonic treatment to obtain a uniform mixed solution, a hydrothermal / solvothermal reaction is carried out, and finally Fe-based MOFs are in situ grown on the surface of the nanofiber membrane to obtain a nanofiber hemodialysis membrane B; wherein the iron metal salt is ferric nitrate or ferric chloride, and the concentration is 0.1-2M; the concentration of the organic ligand is 0.1-4M;

[0012] S2.3: When the organic ligand in S1 comprises: an organic ligand A and an organic ligand B, and the organic ligand A is: melamine or tris(4-aminophenyl)amine, and the organic ligand B is: cyanuric acid, terephthalaldehyde or benzene-1,3,5-tricarbaldehyde, the preparation method is as follows:

[0013] The organic ligand A is dissolved in an organic solvent, the nanofiber membrane obtained in S1 is immersed in the above solution, and then the organic ligand B is added and stirred, and finally COFs are grown in situ on the surface of the nanofiber membrane to obtain a nanofiber hemodialysis membrane C; wherein the concentration of the organic ligand A is 0.1-1M; the concentration of the organic ligand B is 0.1-1M;

[0014] S2.4: When the organic ligand in S1 includes: organic ligand C and organic ligand D, and the organic ligand C is: trimesic acid, 1,3,6,8-tetrakis[p-benzoyl]pyrene or tetrakis(4-sulfophenyl)methane, and the organic ligand D is: melamine or guanidine hydrochloride, the preparation method is as follows:

[0015] The organic ligand C is dissolved in a solvent, the nanofiber membrane obtained in S1 is immersed in the solution, and then the organic ligand D is added, heated and stirred, and finally HOFs are in situ grown on the surface of the nanofiber to obtain the nanofiber hemodialysis membrane D; wherein the concentration of the organic ligand C is 0.1-1M; the concentration of the organic ligand D is 0.1-1M;

[0016] S3: Preparation of efficient functionalized nanofiber hemodialysis membrane

[0017] The four types of nanofiber hemodialysis membranes with in-situ grown crystals obtained in step S2 are treated respectively according to the following methods: the nanofiber hemodialysis membranes are dried and immersed in a mixed solution of water and ethanol, taken out and wiped dry, and then immersed in a mixed solution of ethylenediamine and active molecules, stirred at room temperature for 24-48 hours, and functional active molecules are successfully grafted on the fiber surface through chemical reaction, and finally four types of functionalized nanofiber hemodialysis membranes are obtained, namely: functionalized nanofiber hemodialysis membrane A, functionalized nanofiber hemodialysis membrane B, functionalized nanofiber hemodialysis membrane C, and functionalized nanofiber hemodialysis membrane D;

[0018] Among them, the active molecules described in S1 and S3 include: ferulic acid, caffeic acid, gallic acid, tannic acid, tea polyphenols, curcumin, resveratrol, ellagic acid or L-arginine.

[0019] Preferably, the electrospinning conditions in step S1 are: voltage of 12-20 kV, receiving distance of 10-30 cm, spinneret diameter of 1.0-1.5 mm, ambient temperature of 15-35° C., and humidity of 20-55%.

[0020] Preferably, the ultrasonic treatment time in step S2.1 is 10-30 min, the hydrothermal or solvothermal temperature is set at 90-150° C.; and the reaction time is 6-24 h.

[0021] Preferably, the ultrasonic treatment time in step S2.2 is 10-30 min, the hydrothermal or solvent thermal temperature is set at 120-150° C.; and the reaction time is 6-24 h.

[0022] Preferably, the stirring temperature in step S2.3 is 25-100° C., and the stirring time is 4-8 h.

[0023] Preferably, the drying conditions in step S3 are: temperature of 60-80° C. and time of 6-10 h.

[0024] Preferably, the mass ratio of active molecule, ethylenediamine and water in the mixed solution of ethylenediamine and active molecule in step S3 is (0.1-1):(0.1-0.5):(100-1000).

[0025] In addition, the present invention also provides a functionalized nanofiber hemodialysis membrane prepared according to the method for preparing the functionalized nanofiber hemodialysis membrane.

[0026] Finally, the present invention also provides an application of the above-mentioned high-efficiency functionalized nanofiber hemodialysis membrane in blood purification, and the application is specifically: the nanofiber membrane is applied to a hemodialyzer with a blood purification effect, each of the hemodialyzers comprising: a blood chamber and a dialysate chamber arranged below it and opposite to it, both ends of which are provided with a liquid inlet and a liquid outlet, and bolt holes are provided at the four corners of the blood chamber and the dialysate chamber, and the two are fixed by bolts;

[0027] The bottom of the blood chamber and the top of the dialysate chamber are each provided with at least one alignment installation hole, each of the alignment installation holes is provided with at least one functionalized nanofiber hemodialysis membrane, and the functionalized nanofiber hemodialysis membrane is externally provided with a double-layer sealing gasket, which is sandwiched between the blood chamber and the dialysate chamber;

[0028] The hemodialyzer is divided into a single chamber, a double chamber or a multi-chamber according to the number of the alignment mounting holes, and the therapeutic effect of hemodialysis can be effectively regulated by regulating the thickness of the dialysis membrane and the number of dialysis chambers;

[0029] The functionalized nanofiber hemodialysis membrane is any one of the functionalized nanofiber hemodialysis membrane A, the functionalized nanofiber hemodialysis membrane B, the functionalized nanofiber hemodialysis membrane C, and the functionalized nanofiber hemodialysis membrane D.

[0030] Finally, the present invention also provides a portable hemodialysis machine used in conjunction with the above-mentioned hemodialysis machine, the hemodialysis machine comprising: a shell, the shell is a semi-enclosed body with an open top, an upper cover is hinged on the top, a control unit is arranged on the upper cover, a clamping mechanism is provided at the bottom of the shell for clamping and fixing the hemodialysis machine, a pair of peristaltic pumps are installed above the blood chamber in the hemodialysis machine, one of the peristaltic pumps is used to be connected to the liquid inlet of the blood chamber to provide power for blood delivery, and the other peristaltic pump is connected to the liquid inlet of the dialysate chamber to provide power for dialysate delivery, and the control unit is respectively connected to the two peristaltic pumps;

[0031] Liquid pipeline openings are provided on both sides of the shell for connecting the liquid inlet and the liquid outlet of the hemodialyzer to the outside respectively;

[0032] Handles are provided on both sides of the shell;

[0033] Universal wheels are installed at the four corners of the bottom of the shell.

[0034] Beneficial effects of the present invention

[0035] Compared with the prior art, the present invention uses electrospinning technology to prepare highly efficient functional nanofiber membranes, which can have multiple functions such as adsorption, anti-oxidation, anti-inflammatory, anti-coagulation and antibacterial, effectively improving the removal ability and efficiency of uremic toxins and reducing complications of patients. This functional nanofiber membrane is easy to prepare and the raw materials are easily available, which has broad prospects in the field of hemodialysis materials. In addition, the designed flat-plate nanofiber hemodialyzer and portable hemodialysis machine are simple to operate and lightweight, which is convenient for patients to carry and operate independently. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the SEM image of the functionalized nanofiber hemodialysis membrane prepared in Example 1;

[0037] Figure 2 This is a SEM image of the functionalized nanofiber hemodialysis membrane prepared in Example 3;

[0038] Figure 3 This is a SEM image of the functionalized nanofiber hemodialysis membrane prepared in Example 4;

[0039] Figure 4 It is a comparison chart of free radical scavenging performance of polyacrylonitrile fiber, commercial dialyzer FX-60 and various example materials;

[0040] Figure 5 The graph is a graph of the antibacterial performance of the functionalized nanofiber membrane prepared in Example 1; wherein A is a graph of the antibacterial rate of the material in Example 1, B is a photo of the Escherichia coli plate colony, and C is a photo of the Staphylococcus aureus plate colony;

[0041] Figure 6 The activated partial thromboplastin time graph of each example material;

[0042] Figure 7 This is a structural diagram of a hemodialyzer;

[0043] Figure 8 This is a structural diagram of a multi-chamber hemodialyzer;

[0044] Fig. 9 This is the structural diagram of the hemodialysis machine.

[0045] In the figure,

[0046] 1. Blood chamber; 2. Dialysis fluid chamber; 3. Liquid inlet; 4. Liquid outlet; 5. Alignment mounting hole; 6. Double-layer sealing gasket; 7. Bolt hole; 8. Housing; 9. Upper cover; 10. Control unit; 11. Clamping mechanism; 12. Peristaltic pump; 13. Handle; 14. Liquid pipeline opening; 15. Universal wheel. DETAILED DESCRIPTION

[0047] First, the present invention provides a method for preparing a high-efficiency functionalized nanofiber hemodialysis membrane, the preparation method comprising the following steps:

[0048] S1: Preparation of nanofiber hemodialysis membrane precursor

[0049] A polymer solution is obtained by mixing a polymer with a solvent, wherein the mass fraction of the polymer is 8-20wt%; an organic ligand and an active molecule are respectively added to the above solution, heated and stirred until uniform to obtain an electrospinning solution, wherein the organic ligand is 8-20wt% of the mass fraction of the polymer, and the active molecule is 10-15wt% of the mass fraction of the polymer; the obtained spinning solution is injected into a spinning tube for electrospinning to obtain a nanofiber membrane; preferably, the polymer includes: polyacrylonitrile, polyvinylidene fluoride, polycaprolactone, polylactic acid, cellulose or chitosan; the solvent includes: N,N-dimethylformamide or a mixed solution of N,N-dimethylformamide and acetone or a mixed solution of acetic acid and water or hexafluoroisopropanol; the electrospinning conditions are: voltage of 12-20kV, receiving distance of 10-30cm, spinneret diameter of 1.0-1.5mm, ambient temperature of 15-35°C, and humidity of 20-55%.

[0050] S2: Preparation of crystal-loaded nanofiber membranes

[0051] S2.1: When the organic ligand in S1 is trimesic acid, terephthalic acid, 2-aminoterephthalic acid, pyromellitic acid or fumaric acid, the preparation method is as follows:

[0052] The zirconium metal salt and the organic ligand are added to the solvent respectively, and ultrasonically treated for 10-30 minutes to obtain a uniform mixed solution; the nanofiber membrane obtained in S1 is immersed in the mixed solution for 10-30 minutes, and then the nanofiber membrane and the mixed solution are subjected to a hydrothermal / solvothermal reaction at a temperature of 90-150°C for 6-24 hours, and finally Zr-based MOFs are in situ grown on the surface of the nanofiber membrane to obtain a nanofiber hemodialysis membrane A, wherein the zirconium metal salt is zirconium oxychloride or zirconium chloride, and the concentration is 0.5-3M; the organic ligand concentration is 0.1-3.5M; the solvent is a mixed solution of N,N-dimethylformamide and acetic acid or a mixed solution of N,N-dimethylformamide and formic acid or a N,N-dimethylformamide solution or a mixed solution of water and formic acid;

[0053] S2.2: When the organic ligand in S1 is trimesic acid or terephthalic acid, the preparation method is as follows:

[0054] The iron metal salt and the organic ligand are added to the solvent respectively, and ultrasonically treated for 10-30 minutes to obtain a uniform mixed solution, and then the nanofiber membrane obtained in S1 is completely immersed in the above mixed solution for hydrothermal / solvothermal reaction at a temperature of 120-150°C for 6-24 hours, and finally Fe-based MOFs are in situ grown on the surface of the nanofiber membrane to obtain a nanofiber hemodialysis membrane B; wherein the iron metal salt is ferric nitrate or ferric chloride, and the concentration is 0.1-2M; the organic ligand concentration is 0.1-4M; the solvent is a mixed solution or aqueous solution of N,N-dimethylformamide and acetic acid;

[0055] S2.3: When the organic ligand in S1 comprises: an organic ligand A and an organic ligand B, and the organic ligand A is: melamine or tris(4-aminophenyl)amine, and the organic ligand B is: cyanuric acid, terephthalaldehyde or benzene-1,3,5-tricarbaldehyde, the preparation method is as follows:

[0056] The organic ligand A is dissolved in an organic solvent, the nanofiber membrane obtained in S1 is immersed in the above solution, and then the organic ligand B is added, and stirred at 25-100°C for 4-8h, and finally COFs are grown in situ on the surface of the nanofiber membrane to obtain a nanofiber hemodialysis membrane C; wherein the concentration of the organic ligand A is 0.1-1M; the concentration of the organic ligand B is 0.1-1M; and the organic solvent is dimethyl sulfoxide, N,N-dimethylformamide or N,N-dimethylacetamide;

[0057] S2.4: When the organic ligand in S1 includes: organic ligand C and organic ligand D, and the organic ligand C is: trimesic acid, 1,3,6,8-tetrakis[p-benzoyl]pyrene or tetrakis(4-sulfophenyl)methane, and the organic ligand D is: melamine or guanidine hydrochloride, the preparation method is as follows:

[0058] The organic ligand C is dissolved in a solvent, the nanofiber membrane obtained in S1 is immersed in the solution, and then the organic ligand D is added, and heated and stirred at 40-70°C for 30 minutes, and finally HOFs are in situ grown on the surface of the nanofiber to obtain the nanofiber hemodialysis membrane D; wherein the concentration of the organic ligand C is 0.1-1M; the concentration of the organic ligand D is 0.1-1M;

[0059] S3: Preparation of efficient functionalized nanofiber hemodialysis membrane

[0060] The four types of nanofiber hemodialysis membranes with in-situ grown crystals obtained in step S2 are treated respectively according to the following methods: drying the nanofiber hemodialysis membranes in an oven at 60-80°C for 6-10h, and then immersing them in a mixed solution of water and ethanol, wherein the mass ratio of water to ethanol is 2:1, taking them out and drying them, and then immersing them in a mixed solution of ethylenediamine and active molecules, stirring them at room temperature for 24-48h, and successfully grafting functional active molecules on the fiber surface through chemical reaction, and finally obtaining four types of functionalized nanofiber hemodialysis membranes, namely: functionalized nanofiber hemodialysis membrane A, functionalized nanofiber hemodialysis membrane B, functionalized nanofiber hemodialysis membrane C, and functionalized nanofiber hemodialysis membrane D;

[0061] Among them, the active molecules in S1 and S3 include: ferulic acid, caffeic acid, gallic acid, tannic acid, tea polyphenols, curcumin, resveratrol, ellagic acid or L-arginine. Preferably, the mass ratio of active molecules, ethylenediamine and water in the mixed solution of ethylenediamine and active molecules is (0.1-1): (0.1-0.5): (100-1000).

[0062] In addition, the present invention also provides a functionalized nanofiber hemodialysis membrane prepared according to the method for preparing the functionalized nanofiber hemodialysis membrane.

[0063] Finally, the present invention also provides an application of the functionalized nanofiber hemodialysis membrane in blood purification, which is specifically: applying the nanofiber membrane to a hemodialyzer with a blood purification effect, each of the hemodialyzers comprising: a blood chamber 1 and a dialysate chamber 2 arranged below and opposite to it, both ends of which are provided with a liquid inlet 3 and a liquid outlet 4, and bolt holes 7 are provided at the four corners of the blood chamber 1 and the dialysate chamber 2, and the two are fixed by bolts;

[0064] At least one alignment installation hole 5 is provided at the bottom of the blood chamber 1 and at the top of the dialysate chamber 2. A functionalized nanofiber hemodialysis membrane is provided in each alignment installation hole 5. To prevent leakage during the dialysis process, a double-layer sealing gasket 6 is provided on the outside of the functionalized nanofiber hemodialysis membrane and is sandwiched between the blood chamber 1 and the dialysate chamber 2.

[0065] The hemodialyzer is divided into single-chamber, double-chamber or multi-chamber according to the number of the alignment holes 5 and the functionalized nanofiber hemodialysis membranes. When the number of the alignment holes 5 is one, two or more, the hemodialyzer is divided into single-chamber, double-chamber or multi-chamber. The therapeutic effect of hemodialysis can be regulated by adjusting the thickness of the functionalized nanofiber hemodialysis membrane and the number of dialysis chambers. To facilitate disinfection and avoid leakage, the liquid inlet 3 and the liquid outlet 4 at both ends of the blood chamber 1 and the dialysate chamber 2 adopt an integrated structure. The installed nanofiber hemodialyzer can be connected to the hemodialysis system to complete hemodialysis, thereby achieving the function of removing small and medium-molecule toxins.

[0066] Preferably, the dimensions of the blood chamber 1 and the dialysate chamber 2 are: 70-140 mm in length, 60-80 mm in width, and 20-30 mm in height. The length of the integrated structure pipeline interface is 10-20 mm, and the inner diameter is 8-12 mm.

[0067] The functionalized nanofiber hemodialysis membrane is any one of the functionalized nanofiber hemodialysis membrane A, the functionalized nanofiber hemodialysis membrane B, the functionalized nanofiber hemodialysis membrane C, and the functionalized nanofiber hemodialysis membrane D.

[0068] The hemodialyzer body is made of medical polymer materials, including but not limited to polymethyl methacrylate (PMMA), polycarbonate (PC), polypropylene (PP), polyphenylene sulfone (PPSU), medical TPE materials, etc.

[0069] The filtration mode of the functionalized nanofiber hemodialysis membrane adopts dead-end filtration or cross-flow filtration.

[0070] Furthermore, the hemodialyzer is applied to a hemodialysis machine, which includes: a shell 8, the shell 8 is a semi-enclosed body with an open top, and a top cover 9 is hinged on the top, a control unit 10 is arranged on the top cover 9, a clamping mechanism 11 is provided at the bottom of the shell 8, which is used to clamp and fix the hemodialyzer to maintain the stability of the dialysis process, and a pair of peristaltic pumps 12 are installed above the blood chamber 1 in the hemodialyzer, one of the peristaltic pumps 12 is used to connect with the blood chamber liquid inlet 3, and is used to provide power for blood delivery liquid, and the other peristaltic pump 12 is connected with the liquid inlet 3 of the dialysate chamber, and is used to provide power for dialysate delivery liquid, and the control unit 10 is respectively connected to the two peristaltic pumps 12; the top cover 9 is connected to the shell 8 through two sets of rotating shafts, and in order to avoid corrosion or damage caused by exposed wires, the controller unit 10 is connected to the hemodialyzer through the internal wiring of the shell 8. The peristaltic pump 12 used in the hemodialyzer can make the flow rate of each channel reach 500mL / min, and the blood flow rate and dialysate flow rate can be effectively controlled by detecting and changing the rotation speed of the peristaltic pump.

[0071] Liquid pipeline openings 14 are provided on both sides of the shell 8 for connecting the liquid inlet 3 and the liquid outlet 4 of the hemodialyzer to the outside respectively; and to prevent the liquid pipeline from being entangled or damaged on the outside, the pipeline can be stored inside the dialysis machine and then connected to the outside through the liquid pipeline openings 14.

[0072] The shell 8 adopts a chamfered design for safety reasons. In order to reduce the overall weight of the machine, its material is preferably engineering plastic (such as ABS plastic, polybutylene terephthalate (PBT), polyphenylene ether (PPO), etc.), or special engineering plastic (such as polyether ketone (PEK), polyetheretherketone (PEEK), polyaryletherketone (PAEK)), etc.

[0073] Handles 13 are provided on both sides of the housing 8;

[0074] Universal wheels 15 are installed at the four corners of the bottom of the shell 8 to facilitate medical staff or patients to carry it.

[0075] Example 1

[0076] Polyacrylonitrile (PAN) is added to N,N-dimethylformamide (DMF) solution, wherein the mass fraction of PAN is 12wt%, and magnetic stirring is performed at 45°C for 6h. After complete dissolution, organic ligands (trimethylene tricarboxylic acid (BTC)) and tea polyphenols (TP) are added, wherein BTC is 10wt% of PAN and TP is 15wt% of PAN, and heating and stirring are continued until complete dissolution to obtain a uniform and stable blended solution; the blended solution is loaded into a syringe and electrospun under the conditions of a voltage of 12kV, a receiving distance of 10cm, a spinneret diameter of 1.0mm, an ambient temperature of 15°C, and a humidity of 20%, and deposited for 24h to obtain a PAN composite nanofiber membrane.

[0077] Prepare 60mL of a mixed solution of 0.075M ZrOCl2 and BTC in DMF and HCOOH (DMF:HCOOH=1:1), and ultrasonicate for 15min; immerse the PAN composite nanofiber membrane obtained in the previous step in the mixed solution and continue ultrasonicating for 10min; transfer the PAN composite nanofiber membrane and the mixed solution to a hydrothermal reactor for solvothermal reaction, the reaction temperature is set to 135℃, and the reaction time is 24h. After the reaction is completed, wait for the hydrothermal reactor to cool naturally to room temperature, take out the fiber membrane and rinse it alternately with water and ethanol to obtain a nanofiber membrane loaded with MOF-808;

[0078] The MOF-808 loaded nanofiber membrane obtained in the previous step was dried in an oven at 80°C for 6 h, and then immersed in a mixed solution of water and ethanol, wherein the mass ratio of water to ethanol was 2:1. After being taken out, it was immersed in an aqueous solution of 200 mL of ethylenediamine (100 mg / mL) and TP (1 mg / mL), and stirred at room temperature for 24 h. TP was grafted onto the surface of the fiber membrane through the self-oxidation reaction of Schiff base and polyphenol. After the reaction, the composite fiber was taken out and soaked in hot water several times, then rinsed with ethanol several times, and dried in a 50°C oven overnight to obtain a TP / MOF808 modified nanofiber membrane.

[0079] The obtained TP / MOF-808 functionalized nanofiber membrane has a thickness of 150 μm and has good adsorption performance for uremic toxins. Its adsorption capacity for creatinine can reach 200 mg / g, and its adsorption capacity for p-cresol sulfate can reach 300 mg / g. The composite nanofiber membrane also showed good toxin removal function in the simulated dialysis experiment. The blood flow rate was set at 200-300 mL / min, the dialysate flow rate was set at 400-500 mL / min, and the effective area was 9.6 cm 2 The composite nanofiber membrane with a mass of 145 mg can remove 90-95% of creatinine and 90-93% of p-cresol sulfate within 1 hour, and the retention rate of bovine serum albumin can reach 99.3%; the composite nanofiber membrane has good flexibility and mechanical strength, and can be used as a self-supporting hemodialysis membrane; in addition, the composite nanofiber membrane exhibits good antioxidant ability and can effectively remove free radicals. The removal rate of diphenylpicrylhydrazyl (DPPH) can reach more than 96% within 1 hour, and the removal rate of 2,2'-azobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) can reach more than 97% within 30 minutes; and its antibacterial rate against Staphylococcus aureus and Escherichia coli can reach 99%; the activated thrombin time (APTT) of the composite nanofiber membrane is increased compared with the blank control (31s), and it will not induce coagulation within 205s, and has good anticoagulant activity.

[0080] Example 2

[0081] Add polyvinylidene fluoride (PVDF) to a mixed solution of DMF and acetone and stir until completely dissolved, wherein the mass fraction of PVDF is 15wt%, the volume ratio of DMF and acetone is 2:3, and magnetic stirring is performed at 45°C for 6h, then add organic ligands (fumaric acid (Fum)) and tannic acid (TA), Fum is 10wt% of PVDF, and TA is 10wt% of PVDF, and continue stirring until completely dissolved, and after standing for 2h, a uniform and stable blended solution is obtained; the blended solution is loaded into a syringe and electrospun at 20kV, a receiving distance of 30cm, a spinneret diameter of 1.5mm, an ambient temperature of 35°C, and a humidity of 55%, and deposited for 36h. A PVDF composite nanofiber membrane is obtained.

[0082] Prepare 130mL of 0.1M ZrCl4 and Fum mixed solution of HCOOH and water, where the volume ratio of HCOOH to water is 10:3, and ultrasonically treat for 10 minutes; immerse the PVDF composite nanofiber membrane obtained in the previous step in the mixed solution and continue ultrasonication for 10 minutes; then transfer the PVDF composite nanofiber membrane and the mixed solution to a hydrothermal reactor for solvothermal reaction, the reaction temperature is set to 130℃, and the reaction time is 12 hours. After the reaction is completed, wait for the hydrothermal reactor to cool naturally to room temperature, take out the fiber membrane and rinse it alternately with water and ethanol to obtain a nanofiber membrane loaded with MOF-801 (Zr);

[0083] The MOF-801 (Zr) loaded nanofiber membrane obtained in the previous step was dried in an oven at 60°C for 10 h, and then immersed in a mixed solution of water and ethanol, wherein the mass ratio of water to ethanol was 2:1. After being taken out, it was immersed in an aqueous solution of 200 mL of ethylenediamine (100 mg / mL) and TA (1 mg / mL), and stirred at room temperature for 24 h. TA was grafted onto the fiber surface through the self-oxidation reaction of Schiff base and polyphenol. After the reaction, the composite fiber was taken out and soaked in hot water several times, then rinsed with ethanol several times, and dried in a 50°C oven overnight to obtain a TA / MOF-801 modified nanofiber membrane.

[0084] The obtained TA / MOF-801 functionalized nanofiber membrane has a thickness of 147 μm and has good adsorption performance for uremic toxins, among which the adsorption capacity for creatinine can reach 160 mg / g; the composite nanofiber membrane also showed good toxin removal function in the simulated dialysis experiment, with the blood flow rate set at 200-300 mL / min, the dialysate flow rate at 400-500 mL / min, and the effective area of ​​9.6 cm 2The composite nanofiber membrane with a mass of 157 mg can remove 90-93% of creatinine within 1 hour, can effectively remove uremic toxins, and can retain 99% of bovine serum albumin; it has good flexibility and mechanical strength and can be used as a self-supporting hemodialysis membrane; in addition, the functionalized nanofibers have good antioxidant ability and can effectively remove free radicals. The removal rate of DPPH within 1 hour can reach more than 96%, and the removal rate of ABTS within 30 minutes can reach more than 98%; and its antibacterial rate against Staphylococcus aureus and Escherichia coli can reach 99%; the APTT of the composite nanofiber membrane is increased compared with the blank control (31s), and it will not induce coagulation within 223s, and has good anticoagulant activity.

[0085] Example 3

[0086] Polyacrylonitrile (PAN) is added to N,N-dimethylformamide (DMF) solution, wherein the mass fraction of PAN is 12wt%, and magnetic stirring is performed at 45°C for 6h. After complete dissolution, organic ligands (2,6-naphthalene dicarboxylic acid (2,6-NDA)) and caffeic acid (NA) are added, wherein 2,6-NDA is 10wt% of PAN and NA is 12wt% of PAN. Heating and stirring are continued until complete dissolution to obtain a uniform and stable blended solution; the blended solution is loaded into a syringe and electrospun under the conditions of a voltage of 15kV, a receiving distance of 20cm, a spinneret diameter of 1.2mm, an ambient temperature of 20°C, and a humidity of 30%, and deposited for 24h to obtain a PAN composite nanofiber membrane.

[0087] Prepare 90mL of 1.62mM ZrCl4 and 2.28mM 2,6-NDA DMF solution and sonicate for 15 minutes. Immerse the PAN composite nanofiber membrane obtained in the previous step in the above mixed solution and continue sonication for 15 minutes; transfer the above PAN composite nanofiber membrane mixed solution to a hydrothermal reactor for solvothermal reaction. The reaction temperature is set to 80°C and the reaction time is 18 hours. After the reaction is completed, wait for the hydrothermal reactor to cool naturally to room temperature, then take out the fiber membrane and rinse it alternately with water and acetone to obtain a nanofiber membrane loaded with UIO-NDC;

[0088] The UIO-NDC loaded nanofiber membrane obtained in the previous step was dried in an oven at 70°C for 8 h, and then immersed in a mixed solution of water and ethanol, wherein the mass ratio of water to ethanol was 2:1. After being taken out, it was immersed in an aqueous solution of 200 mL of ethylenediamine (100 mg / mL) and NA (1 mg / mL), and stirred at room temperature for 24 h. NA was grafted onto the surface of the fiber membrane through the self-oxidation reaction of Schiff base and polyphenol. After the reaction, the composite fiber was taken out and soaked in hot water several times, then rinsed with ethanol several times, and dried in a 50°C oven overnight to obtain a NA / UIO-NDC modified nanofiber membrane.

[0089] The obtained NA / UIO-NDC functionalized nanofiber membrane has a thickness of 145 μm and has good adsorption performance for uremic toxins. Its adsorption capacity for creatinine can reach 150 mg / g, and its adsorption capacity for p-cresol sulfate can reach 275 mg / g. The composite nanofiber membrane also showed good toxin removal function in the simulated dialysis experiment. The blood flow rate was set at 200-300 mL / min, the dialysate flow rate was set at 400-500 mL / min, and the effective area was 9.6 cm 2 The composite nanofiber membrane with a mass of 160 mg can remove 90-95% of creatinine and 90-93% of p-cresol sulfate within 1 hour, and the retention rate of bovine serum albumin can reach more than 99.2%; the composite nanofiber membrane has good flexibility and mechanical strength and can be used as a self-supporting hemodialysis membrane; in addition, the composite nanofiber membrane exhibits good antioxidant ability and can effectively remove free radicals. The removal rate of DPPH within 1 hour can reach more than 94%, and the removal rate of ABTS within 30 minutes can reach more than 97%; and its antibacterial rate against Staphylococcus aureus and Escherichia coli can reach 99%; the APTT of the composite nanofiber membrane is increased compared with the blank control (31s), and it will not induce coagulation within 211s, and has good anticoagulant activity.

[0090] Example 4

[0091] Polycaprolactone (PCL) was added to a mixed solution of acetic acid and water, wherein the mass fraction of PCL was 12wt%, and magnetic stirring was performed at room temperature for 12h. After complete dissolution, organic ligands (trimethylenediamine (BTC)) and ferulic acid (FA) were added, wherein BTC was 12wt% of PAN and FA was 12wt% of PAN. Heating and stirring were continued until complete dissolution to obtain a uniform and stable spinning solution. The spinning solution was loaded into a syringe and electrospun under the conditions of a voltage of 12kV, a receiving distance of 10cm, a spinneret diameter of 1.0mm, an ambient temperature of 15°C, and a humidity of 20%. The solution was deposited for 24h to obtain a PCL nanofiber membrane.

[0092] The PCL nanofiber membrane obtained in the previous step was immersed in a DMF solution of tri(4-aminophenyl)amine (TAPA), wherein the concentration of TAPA was 0.1 M, and then p-diphenylaldehyde (PDA) was added, wherein the concentration of PDA was 0.3 M, and stirred at 100°C for 4 h to obtain a nanofiber membrane loaded with TAPA-PDA COF;

[0093] The TAPA-PDA COF loaded nanofiber membrane obtained in the previous step was dried in an oven at 80°C for 6 h, and then immersed in a mixed solution of water and ethanol, wherein the mass ratio of water to ethanol was 2:1. After being taken out, it was immersed in an aqueous solution of 200 mL of ethylenediamine (100 mg / mL) and FA (1 mg / mL), and stirred at room temperature for 24 h. FA was grafted onto the surface of the fiber membrane through the self-oxidation reaction of Schiff base and polyphenol. After the reaction, the composite fiber was taken out and immersed in hot water for several times, and then rinsed with ethanol for several times, and dried in an oven at 50°C overnight to obtain a FA / TAPA-PDA COF modified nanofiber membrane.

[0094] The obtained FA / TAPA-PDA COF functionalized nanofiber membrane has a thickness of 195 μm and exhibits good adsorption performance for uremic toxins. Through adsorption kinetics and adsorption isotherms, it can be calculated that the adsorption capacity for creatinine can reach 120 mg / g, and the adsorption capacity for p-cresol sulfate can reach 80 mg / g; the composite nanofiber membrane also exhibits good toxin removal function in the simulated dialysis experiment, setting the blood flow rate at 200-300 mL / min, the dialysate flow rate at 400-500 mL / min, and the effective area at 9.6 cm 2 The composite nanofiber membrane with a mass of 182 mg can remove 89-92% of creatinine and 80-86% of urea within 4 hours, and the retention rate of bovine serum albumin can reach 99%; it has good flexibility and mechanical strength and can be used as a self-supporting hemodialysis membrane; in addition, the functionalized nanofibers have good antioxidant ability and can effectively remove free radicals. The removal rate of DPPH within 1 hour can reach more than 96%, and the removal rate of ABTS within 30 minutes can reach more than 98%; and its antibacterial rate against Staphylococcus aureus and Escherichia coli can reach 98%; the APTT of the composite nanofiber membrane is increased compared with the blank control (31s), and it will not induce coagulation within 203s, and has good anticoagulant activity.

[0095] Example 5

[0096] PCL was added to a mixed solution of acetic acid and water, wherein the mass fraction of PCL was 15wt%, and magnetic stirring was performed at room temperature for 18h. After complete dissolution, 1,3,6,8-tetra[p-benzoyl]pyrene (H4TBAPy) and gallic acid (GA) were added, wherein H4TBAPy was 10wt% of PCL and GA was 10wt% of PCL. Stirring was continued until complete dissolution, and a uniform and stable spinning solution was obtained after standing for 12h. The spinning solution was loaded into a syringe and electrospun under the conditions of a voltage of 15kV, a receiving distance of 20cm, a spinneret diameter of 1.2mm, an ambient temperature of 20°C, and a humidity of 30%. After deposition for 36h, a PCL composite nanofiber membrane was obtained.

[0097] The PCL composite nanofibers obtained in the previous step were immersed in 200 mL of 0.1 M H4TBAPy in DMF solution, and then guanidine hydrochloride was added, wherein the concentration of guanidine hydrochloride was 0.3 M, and stirred at room temperature for 48 h to obtain a nanofiber membrane loaded with PCF-1;

[0098] The PCF-1 loaded nanofiber membrane obtained in the previous step was dried in an oven at 80°C for 6 h, and then immersed in a mixed solution of water and ethanol, wherein the mass ratio of water to ethanol was 2:1. After being taken out, it was immersed in an aqueous solution of 200 mL of ethylenediamine (100 mg / mL) and GA (1 mg / mL), and stirred at room temperature for 24 h. GA was grafted onto the fiber surface through the self-oxidation reaction of Schiff base and polyphenol. After the reaction, the composite fiber was taken out and immersed in hot water several times, and then rinsed with ethanol several times, and dried in a 50°C oven overnight to obtain a GA / PFC-1 modified nanofiber membrane.

[0099] The obtained GA / PFC-1 functionalized nanofiber membrane has a thickness of 178 μm and exhibits good adsorption performance for uremic toxins. The adsorption capacity for creatinine can reach 100 mg / g, and the adsorption capacity for hippuric acid can reach 80 mg / g. The composite nanofiber membrane also exhibits good toxin removal function in the simulated dialysis experiment. The blood flow rate is set at 200-300 mL / min, the dialysate flow rate is set at 400-500 mL / min, and the effective area is 9.6 cm 2 The composite nanofiber membrane with a mass of 143 mg can remove 89-93% of creatinine and 83-87% of urea in 4 hours, and the retention rate of bovine serum albumin can reach more than 99.4%; it has good flexibility and mechanical strength and can be used as a self-supporting hemodialysis membrane; in addition, the functionalized nanofiber has good antioxidant capacity and can effectively remove free radicals. The removal rate of DPPH can reach more than 92% within 1 hour, and the removal rate of ABTS can reach more than 96% within 30 minutes; and it can achieve 99% antibacterial rate against Staphylococcus aureus and Escherichia coli; the APTT of the composite nanofiber membrane is increased compared with the blank control (31s), and it will not induce coagulation within 207s, and has good anticoagulant activity.

[0100] Example 6

[0101] Polyacrylonitrile (PAN) is added to N,N-dimethylformamide (DMF) solution, wherein the mass fraction of PAN is 10wt%, and magnetic stirring is performed at 45°C for 6h. After complete dissolution, organic ligands (trimesic acid (BTC)) and ellagic acid (EA) are added, wherein BTC is 12wt% of PAN and EA is 10wt% of PAN, and heating and stirring are continued until complete dissolution to obtain a uniform and stable blended solution; the blended solution is loaded into a syringe and electrospun under the conditions of a voltage of 15kV, a receiving distance of 20cm, a spinneret diameter of 1.2mm, an ambient temperature of 20°C, and a humidity of 30%, and deposited for 24h to obtain a PAN composite nanofiber membrane.

[0102] Prepare 60mL of 6mM Fe(NO3)3·9H2O and BTC DMF solution and ultrasonically treat for 20min. The PAN composite nanofiber membrane obtained above is completely immersed in the mixed solution and transferred to a hydrothermal reactor for solvothermal reaction. The reaction temperature is set to 120℃ and the reaction time is 24h. After the reaction is completed, wait for the hydrothermal reactor to cool naturally to room temperature, then take out the fiber membrane and rinse it alternately with water and acetone to obtain a nanofiber membrane loaded with MIL-100(Fe);

[0103] The nanofiber membrane loaded with MIL-100(Fe) obtained in the previous step was dried in an oven at 80°C for 6 h, and then immersed in a mixed solution of water and ethanol, wherein the mass ratio of water to ethanol was 2:1. After being taken out, it was immersed in an aqueous solution of 300 mL of ethylenediamine (100 mg / mL) and ellagic acid (1 mg / mL), and stirred at room temperature for 24 h. EA was grafted onto the surface of the fiber membrane through the self-oxidation reaction of Schiff base and polyphenols. After the reaction, the composite fiber was taken out and soaked in hot water several times, then rinsed with ethanol several times, and dried in an oven at 50°C overnight to obtain an EA / MIL-100(Fe) modified nanofiber membrane.

[0104] The obtained EA / M IL-100(Fe) functionalized nanofiber membrane has a thickness of 180 μm and has good adsorption performance for uremic toxins. Its adsorption capacity for creatinine can reach 100 mg / g, and its adsorption capacity for p-cresol sulfate can reach 150 mg / g. The composite nanofiber membrane also showed good toxin removal function in the simulated dialysis experiment. The blood flow rate was set at 200-300 mL / min, the dialysate flow rate was set at 400-500 mL / min, and the effective area was 9.6 cm 2The composite nanofiber membrane with a mass of 139 mg can remove 90-95% of creatinine and 89-92% of p-cresol sulfate within 1 hour, and the retention rate of bovine serum albumin can reach 99%; the composite nanofiber membrane has good flexibility and mechanical strength and can be used as a self-supporting hemodialysis membrane; in addition, the composite nanofiber membrane exhibits good antioxidant ability and can effectively remove free radicals. The DPPH removal rate can reach more than 92% within 1 hour, and the ABTS removal rate can reach more than 95% within 30 minutes; and its antibacterial rate against Staphylococcus aureus and Escherichia coli can reach 99%; the APTT of the composite nanofiber membrane is increased compared with the blank control (31s), and it will not induce coagulation within 215s, and has good anticoagulant activity.

[0105] Example 7

[0106] The hemodialyzer and hemodialysis machine with blood purification effect are further described below through specific examples, but the implementation mode of the present invention is not limited thereto and cannot be understood as limiting the protection scope of the present invention.

[0107] The present invention provides a hemodialyzer using the highly efficient functionalized nanofiber hemodialysis membrane, the hemodialyzer comprising: a blood chamber 1 and a dialysate chamber 2 arranged below and opposite to the blood chamber 1, both ends of which are provided with a liquid inlet 3 and a liquid outlet 4, the four corners of the blood chamber 1 and the dialysate chamber 2 are provided with bolt holes 7 and the two are fixed by bolts;

[0108] The bottom of the blood chamber 1 and the top of the dialysate chamber 2 are each provided with two alignment mounting holes 5, each of which is provided with a functionalized nanofiber hemodialysis membrane. To prevent leakage during the dialysis process, a double-layer sealing gasket 6 is provided on the outside of the functionalized nanofiber hemodialysis membrane and is sandwiched between the blood chamber 1 and the dialysate chamber 2;

[0109] like Figure 8 As shown, the hemodialyzer has a double-chamber structure. To facilitate disinfection and avoid leakage, the liquid inlet 3 and the liquid outlet 4 at both ends of the blood chamber 1 and the dialysate chamber 2 adopt an integrated structure. The installed nanofiber hemodialyzer can be connected to the hemodialysis system to complete hemodialysis and achieve the function of removing small and medium-molecule toxins.

[0110] Preferably, the dimensions of the blood chamber 1 and the dialysate chamber 2 are: 70-140 mm in length, 60-80 mm in width, and 20-30 mm in height. The length of the integrated structure pipeline interface is 10-20 mm, and the inner diameter is 8-12 mm.

[0111] The functionalized nanofiber hemodialysis membrane is any one of the functionalized nanofiber hemodialysis membrane A, the functionalized nanofiber hemodialysis membrane B, the functionalized nanofiber hemodialysis membrane C, and the functionalized nanofiber hemodialysis membrane D.

[0112] The hemodialyzer body is made of medical polymer materials, including but not limited to polymethyl methacrylate (PMMA), polycarbonate (PC), polypropylene (PP), polyphenylene sulfone (PPSU), medical TPE materials, etc.

[0113] The functionalized nanofiber hemodialysis membrane is filtered in a dead-end filtering mode or a cross-flow filtering mode.

[0114] Further, the hemodialyzer is applied to a hemodialysis machine, such as Fig. 9 As shown, the hemodialysis machine includes: a shell 8, the shell 8 is a semi-enclosed body with an open top, and an upper cover 9 is hinged on the top. A control unit 10 is arranged on the upper cover 9. A U-shaped clamping mechanism 11 is provided at the bottom of the shell 8 for clamping and fixing the hemodialyzer to maintain the stability of the dialysis process. A pair of peristaltic pumps 12 are installed above the blood chamber 1 in the hemodialyzer, one of the peristaltic pumps 12 is used to connect with the liquid inlet 3 of the blood chamber 1 to provide power for blood delivery liquid, and the other peristaltic pump 12 is connected with the liquid inlet 3 of the dialysate chamber 2 to provide power for dialysate delivery liquid, and the two peristaltic pumps 12 drive in opposite directions, so that the blood and dialysate move in opposite directions; the control unit 10 is respectively connected to the two peristaltic pumps 12; used to control their start and stop; the upper cover 9 is connected to the shell 8 through two sets of rotating shafts, and in order to avoid corrosion or damage caused by exposed wires, the controller unit 10 is connected to the hemodialyzer through the internal wiring of the shell 8. The peristaltic pump 12 used in the hemodialyzer can make the flow rate of each channel reach 500mL / min, and the blood flow rate and dialysate flow rate can be effectively controlled by detecting and changing the rotation speed of the peristaltic pump.

[0115] Liquid pipeline openings 14 are provided on both sides of the shell 8 for connecting the liquid inlet 3 and the liquid outlet 4 of the hemodialyzer to the outside respectively; and to prevent the liquid pipeline from being entangled or damaged on the outside, the pipeline can be stored inside the dialysis machine and then connected to the outside through the liquid pipeline openings 14.

[0116] The shell 8 adopts a chamfered design for safety reasons. In order to reduce the overall weight of the machine, its material is preferably engineering plastic (such as ABS plastic, polybutylene terephthalate (PBT), polyphenylene ether (PPO), etc.), or special engineering plastic (such as polyether ketone (PEK), polyetheretherketone (PEEK), polyaryletherketone (PAEK)), etc.

[0117] Handles 13 are provided on both sides of the housing 8;

[0118] Universal wheels 15 are installed at the four corners of the bottom of the shell 8 to facilitate medical staff or patients to carry it.

[0119] Example 8

[0120] The technical solution in this embodiment is substantially the same as the technical solution described in Example 7, the difference being that the hemodialyzer is a single-chamber structure. Figure 7 shown.

Claims

1. A method for preparing a functionalized nanofiber hemodialysis membrane, characterized in that: The preparation method comprises the following steps: S1: Preparation of nanofiber hemodialysis membrane precursor The polymer and the solvent are mixed to obtain a polymer solution, wherein the mass fraction of the polymer is 8-20wt%; the organic ligand and the active molecule are respectively added to the above solution, heated and stirred until uniform to obtain an electrospinning solution, wherein the organic ligand is 8-20wt% of the mass fraction of the polymer, and the active molecule is 10-15wt% of the mass fraction of the polymer; the obtained spinning solution is injected into a spinning tube for electrospinning to obtain a nanofiber membrane; S2: Preparation of a crystal-loaded nanofiber membrane, the preparation method comprising S2.1, S2.2, S2.3 or S2.4; S2.1: When the organic ligand in S1 is trimesic acid, terephthalic acid, 2-aminoterephthalic acid, pyromellitic acid or fumaric acid, the preparation method is as follows: The zirconium metal salt and the organic ligand are added to the solvent respectively, and ultrasonic treatment is performed to obtain a uniform mixed solution; the nanofiber membrane obtained in S1 is immersed in the mixed solution for 10-30 minutes and then subjected to a hydrothermal / solvothermal reaction, and finally Zr-based MOFs are in situ grown on the surface of the nanofiber membrane to obtain a nanofiber hemodialysis membrane A, wherein the zirconium metal salt is zirconium oxychloride or zirconium chloride, and the concentration is 0.5-3M; the organic ligand concentration is 0.1-3.5M; S2.2: When the organic ligand in S1 is trimesic acid or terephthalic acid, the preparation method is as follows: The iron metal salt and the organic ligand are added to the solvent respectively, and ultrasonically treated to obtain a uniform mixed solution, and then the nanofiber membrane obtained in S1 is completely immersed in the above mixed solution to perform a hydrothermal / solvent reaction, and finally Fe-based MOFs are in situ grown on the surface of the nanofiber membrane to obtain a nanofiber hemodialysis membrane B; wherein the iron metal salt is ferric nitrate or ferric chloride, and the concentration is 0.1-2M; the concentration of the organic ligand is 0.1-4M; S2.3: When the organic ligand in S1 comprises: an organic ligand A and an organic ligand B, and the organic ligand A is: melamine or tris(4-aminophenyl)amine, and the organic ligand B is: cyanuric acid, terephthalaldehyde or benzene-1,3,5-tricarbaldehyde, the preparation method is as follows: The organic ligand A is dissolved in an organic solvent, the nanofiber membrane obtained in S1 is immersed in the above solution, and then the organic ligand B is added and stirred, and finally COFs are grown in situ on the surface of the nanofiber membrane to obtain a nanofiber hemodialysis membrane C; wherein the concentration of the organic ligand A is 0.1-1M; the concentration of the organic ligand B is 0.1-1M; S2.4: When the organic ligand in S1 includes: organic ligand C and organic ligand D, and the organic ligand C is: trimesic acid, 1,3,6,8-tetrakis[p-benzoyl]pyrene or tetrakis(4-sulfophenyl)methane, and the organic ligand D is: melamine or guanidine hydrochloride, the preparation method is as follows: The organic ligand C is dissolved in a solvent, the nanofiber membrane obtained in S1 is immersed in the solution, and then the organic ligand D is added, heated and stirred, and finally HOFs are in situ grown on the surface of the nanofiber to obtain the nanofiber hemodialysis membrane D; wherein the concentration of the organic ligand C is 0.1-1M; the concentration of the organic ligand D is 0.1-1M; S3: Preparation of efficient functionalized nanofiber hemodialysis membrane The four types of nanofiber hemodialysis membranes with in-situ grown crystals obtained in step S2 are treated respectively according to the following methods: the nanofiber hemodialysis membranes are dried and immersed in a mixed solution of water and ethanol, taken out and wiped dry, and then immersed in a mixed solution of ethylenediamine and active molecules, stirred at room temperature for 24-48 hours, and functional active molecules are successfully grafted on the fiber surface through chemical reaction, and finally four types of functionalized nanofiber hemodialysis membranes are obtained, namely: functionalized nanofiber hemodialysis membrane A, functionalized nanofiber hemodialysis membrane B, functionalized nanofiber hemodialysis membrane C, and functionalized nanofiber hemodialysis membrane D; Wherein, the active molecules described in S1 and S3 include: ferulic acid, caffeic acid, gallic acid, tannic acid, tea polyphenols, curcumin, resveratrol or ellagic acid.

2. The method for preparing a functionalized nanofiber hemodialysis membrane according to claim 1, characterized in that: The electrospinning conditions in step S1 are: voltage of 12-20 kV, receiving distance of 10-30 cm, spinneret diameter of 1.0-1.5 mm, ambient temperature of 15-35° C., and humidity of 20-55%.

3. The method for preparing a functionalized nanofiber hemodialysis membrane according to claim 1, characterized in that: The ultrasonic treatment time in step S2.1 is 10-30 min, the hydrothermal or solvothermal temperature is set at 90-150° C.; the reaction time is 6-24 h.

4. The method for preparing a functionalized nanofiber hemodialysis membrane according to claim 1, characterized in that: The ultrasonic treatment time in step S2.2 is 10-30 min, the hydrothermal or solvent thermal temperature is set at 120-150° C.; the reaction time is 6-24 h.

5. The method for preparing a functionalized nanofiber hemodialysis membrane according to claim 1, characterized in that: The stirring temperature in step S2.3 is 25-100° C. and the stirring time is 4-8 h.

6. The method for preparing a functionalized nanofiber hemodialysis membrane according to claim 1, characterized in that: The drying conditions in step S3 are: temperature of 60-80° C. and time of 6-10 h.

7. The method for preparing a functionalized nanofiber hemodialysis membrane according to claim 1, characterized in that: The mass ratio of active molecule, ethylenediamine and water in the mixed solution of ethylenediamine and active molecule in step S3 is (0.1-1): (0.1-0.5): (100-1000).

8. The functionalized nanofiber hemodialysis membrane obtained by the preparation method of the functionalized nanofiber hemodialysis membrane according to any one of claims 1 to 7.

9. The use of the functionalized nanofiber hemodialysis membrane in blood purification according to claim 8, characterized in that: The functionalized nanofiber hemodialysis membrane is applied to a hemodialyzer having a blood purification effect, each of the hemodialyzers comprising: a blood chamber (1) and a dialysate chamber (2) arranged below and opposite to the blood chamber, both ends of which are provided with a liquid inlet (3) and a liquid outlet (4), and bolt holes (7) are provided at the four corners of the blood chamber (1) and the dialysate chamber (2), and the two are fixed by bolts; At least one alignment installation hole (5) is provided at the bottom of the blood chamber (1) and at the top of the dialysate chamber (2), at least one functionalized nanofiber hemodialysis membrane is provided in each alignment installation hole (5), and a double-layer sealing gasket (6) is provided on the outside of the functionalized nanofiber hemodialysis membrane and is sandwiched between the blood chamber (1) and the dialysate chamber (2); The hemodialysis machine is divided into a single chamber, a double chamber or a multi-chamber according to the number of the alignment mounting holes (5), and the therapeutic effect of hemodialysis is regulated by adjusting the thickness of the dialysis membrane and the number of dialysis chambers; The functionalized nanofiber hemodialysis membrane is any one of the functionalized nanofiber hemodialysis membrane A, the functionalized nanofiber hemodialysis membrane B, the functionalized nanofiber hemodialysis membrane C, and the functionalized nanofiber hemodialysis membrane D.

10. The use of the functionalized nanofiber hemodialysis membrane in blood purification according to claim 9, characterized in that: The hemodialyzer is applied to a hemodialysis machine, the hemodialysis machine comprising: a housing (8), the housing (8) being a semi-enclosed body with an open top, the top of which is hingedly connected to an upper cover (9), a control unit (10) being arranged on the upper cover (9), a clamping mechanism (11) being provided at the bottom of the housing (8) for clamping and fixing the hemodialyzer, a pair of peristaltic pumps (12) being installed above the blood chamber (1) in the hemodialyzer, one of the peristaltic pumps (12) being connected to the liquid inlet (3) of the blood chamber (1) for providing power for blood transport, the other peristaltic pump (12) being connected to the liquid inlet (3) of the dialysate chamber (2) for providing power for dialysate transport, and the control unit (10) being connected to the two peristaltic pumps (12) respectively; Both sides of the housing (8) are provided with liquid pipeline openings (14) for respectively connecting the liquid inlet (3) and the liquid outlet (4) of the hemodialyzer to the outside; Handles (13) are provided on both sides of the housing (8); Universal wheels (15) are installed at the four corners of the bottom of the housing (8).